ANALISIS FAKTOR–FAKTOR YANG MEMPENGARUHI ABNORMAL RETURN SAHAM PADA KINERJA JANGKA PANJANG PENAWARAN UMUM PERDANA (IPO) (Studi Kasus pada Perusahaan Non Finansial yang Go Public di Bursa Efek Indonesia Tahun 2006-2009) - Abid, Muhammad Talkhisul; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2013)
The average stocks return of the initial public offering (IPO) in the U.S. stockmarket was -29.13% at the end of the third year after the IPO (Ritter, 1991). Theconclusion is that the Underperformed phenomenon is influenced by the volume of tradeand only occurs in the non-financial sector (Ritter, 1991). Underperformed is a stockreturn of initial public offerings that have lower performance compared to the marketreturn. Bessler and Thies (2007) stated that the year of going public is the time period ofthe initial public offering (IPO). There is a time variation in the pattern of benefits, itraises a question of whether companies can maximize the value and amount of fundsacquired. In investing, investors consider the return and risk, the expected results of theinvestment will be realized after a certain period of time and during this period there is arisk of the investments made. The aim of this study is to analyze the factors that affectAbnormal Return on long-term stock performance after 36 months of the IPO. Theindependent variables in this study consist of Benchmark, Money Raised, Market Value,and Magnitude of Underpricing. The dependent variable is the abnormal return on longtermstock performance after 36 months of the IPO.The samples used in this study were the nonfinancial companies on 2006-2009period as many as 54 non-financial companies using purposive sampling method. Theanalysis technique used was multiple linear regression analysis and performed classicalassumption test which include normality test, multicollinearity test, autocorrelation test,and heteroskesdasticity test.The results showed that partially the Benchmark affect significantly and negativelytoward Abnormal Return; Money Raised and Market Value does not affect significantlyand positively towards Abnormal Return; Magnitude of Underpricing affect significantlyand positively towards Abnormal Return. The ability of the four independent variables toexplain the variation on the dependent variables amounted to 45.8%, while the rest equalto 54.2% explained by other factors that are not described in the model.